Rac1, A Potential Target for Tumor Therapy - Liang, Jiaxin; Oyang, Linda; Rao, Shan; Han, Yaqian; Luo, Xia; Yi, Pin; Lin, Jinguan; Xia, Longzheng; Hu, Jiaqi; Tan, Shiming; Tang, Lu; Pan, Qing; et al. (Frontiers in Oncology, 2021)
RAS-related C3 botulinum toxin substrate 1 (Rac.1) is one of the important members of Rho GTPases. It is well known that Rac1 is a cytoskeleton regulation protein that regulates cell adhesion, morphology, and movement. Rac1 is highly expressed in different types of tumors, which is related to poor prognosis. Studies have shown that Rac1 not only participates in the tumor cell cycle, apoptosis, proliferation, invasion, migration and angiogenesis, but also participates in the regulation of tumor stem cell, thus promoting the occurrence of tumors. Rac1 also plays a key role in anti-tumor therapy and participates in immune escape mediated by the tumor microenvironment. In addition, the good prospects of Rac1 inhibitors in cancer prevention and treatment are exciting. Therefore, Rac1 is considered as a potential target for the prevention and treatment of cancer. The necessity and importance of Rac1 are obvious, but it still needs further study.